2022
DOI: 10.1186/s12870-022-03501-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression characterization and cross-species complementation uncover the functional conservation of YABBY genes for leaf abaxial polarity and carpel polarity establishment in Saccharum spontaneum

Abstract: Background Cell polarity establishment and maintenance is indispensable for plant growth and development. In plants, the YABBY transcription factor family has a distinct role in leaf asymmetric polarity establishment and lateral organ initiation. However, for the important sugar crop Saccharum, little information on YABBY genes is available. Results In this study, a total of 20 sequences for 7 SsYABBY genes were identified in the sugarcane genome, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…We found TFBSs for different families of transcription factors related to leaf growth such as the YABBY family genes that have been associated with adaxial and abaxial leaf formation and expansion [ 44 ], not only in Arabidopsis but also in other species [ 45 , 46 , 47 ]. Another important TFBS family identified is the TEOSINTE BRANCHED1/CYCLOIDEA/PROLIFERATING CELL FACTOR (TCP) transcription factor family that has been characterized to participate in leaf size control and act in cyclin activation for leaf endoreplication [ 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found TFBSs for different families of transcription factors related to leaf growth such as the YABBY family genes that have been associated with adaxial and abaxial leaf formation and expansion [ 44 ], not only in Arabidopsis but also in other species [ 45 , 46 , 47 ]. Another important TFBS family identified is the TEOSINTE BRANCHED1/CYCLOIDEA/PROLIFERATING CELL FACTOR (TCP) transcription factor family that has been characterized to participate in leaf size control and act in cyclin activation for leaf endoreplication [ 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The variations in WRKY gene architecture align with its functional diversity ( Bakshi and Oelmuller, 2014 ; Zhu, 2016 ; Wani et al, 2021 ), and/or the acquisition of a novel function during the evolutionary progress. Moreover, gene duplication events, including tandem duplication, segmental duplication and whole-genome duplication, are significant factors influencing gene evolution ( Qiao et al, 2018 ; She et al, 2022 ). This study found 17 (6 segmental and 11 tandem) duplication gene pairs in HcWRKY genes, and the evolutionary dates of these duplicated HcWRKY genes were also estimated using Ks as the proxy for time, the results showed that kenaf duplication events for kenaf 6 of 17 pairs occurred within the past 12.385-165.717 million years ( Supplementary Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, HcWRKY44 was selected as a candidate for further functional characterization. We transformed HcWRKY44 into Arabidopsis instead of kenaf because Arabidopsis plants have frequently been used in transgenic studies for gene function investigation for crops that are challenging for gene transformation ( Niu et al, 2012 , 2022 ; Luo et al, 2013 ; She et al, 2022 ). In transgenic lines, overexpression of HcWRKY44 increased salinity stress tolerance, as evidenced by longer roots, more lateral roots and a greater survival rate ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…YABBY s, as plant-specific gene family, encode a family of TRs containing two conserved domains: a C2C2-type zinc finger domain in the N-terminal region, and a helix-loop-helix YABBY domain (helix-loop-helix motif) in the C-terminal region ( Bowman, 2000 ; Jang et al, 2004 ). Most members of YABBY family are expressed in a polar manner in lateral organs and involved in developmental processes such as leaf growth, floral organ development, leaf margin establishment and polarity maintenance ( Hou, Lin & Hou, 2020 ; Kang et al, 2022 ; She et al, 2022 ; Yang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%